2022
DOI: 10.1371/journal.pone.0269731
|View full text |Cite
|
Sign up to set email alerts
|

Detection of features predictive of microRNA targets by integration of network data

Abstract: Gene activity is controlled by multiple molecular mechanisms, for instance through transcription factors or by microRNAs (miRNAs), among others. Established bioinformatics tools for the prediction of miRNA target genes face the challenge of ensuring accuracy, due to high false positive rates. Further, these tools present poor overlap. However, we demonstrated that it is possible to filter good predictions of miRNA targets from the bulk of all predictions by using information from the gene regulatory network. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Thus, the presence and distribution of various CREs in VraRBOH gene promoters suggested that the VraRBOH genes might have involved in regulation of various biological activities including drought stress response in mung bean. The miRNA databases provide the insights into exploration of the plant genome for identifying miRNA targets and regulation of miRNA based gene regulations (Guo et al 2019;Yasin et al 2020;Cihan et al 2022). We identi ed 16 miRNAs targeting ve VraRBOH genes in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the presence and distribution of various CREs in VraRBOH gene promoters suggested that the VraRBOH genes might have involved in regulation of various biological activities including drought stress response in mung bean. The miRNA databases provide the insights into exploration of the plant genome for identifying miRNA targets and regulation of miRNA based gene regulations (Guo et al 2019;Yasin et al 2020;Cihan et al 2022). We identi ed 16 miRNAs targeting ve VraRBOH genes in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…integrates information from 3 of 16 multiple prediction algorithms to get accurate results but it often worsens the inference [33]. This necessitates experimental validation to check the interaction between miRNA and its target mRNA directly [24] or computational methods that would learn from the true positive results of the existing large databases [34]. However, recent databases such as mirDIP 4.1 [35] claims to provide more accurate miRNA-target predictions by combining predictions from 30 independent resources using integrative score.…”
Section: Introductionmentioning
confidence: 99%